White wine, sparkling white wine and black caviar – The sensory experience of pairing of flavours - K. Wendin; B. Collin; S. Forsberg; H. Scander; R. Albin; F. Åhrberg; T. Ranta (International Journal of Gastronomy and Food Science, 2026)

Impact of dietary selenium supplementation on growth performance, bioaccumulation, antioxidant capacity, and gene expression in GIFT strain of Nile Tilapia (Oreochromis niloticus) - Albin Jemila Thangarani; Nathan Felix; Arul Victor Suresh; Ayyathurai Kathirvelpandian; Seerappalli Aran Shanmugam; Rajagopal Ramya; Paul Nathaniel T.; Irudhayavimalan Jegan Michael Andro Jeevagan; Thodhal Yoganandham Suman (Aquaculture International, 2024)

Gaseous contaminant transfer in membrane-based air-to-air energy exchangers - Ashwin Joseph Mathews; Easwaran N. Krishnan; Albin Joseph; Gurubalan Annadurai; Melanie T. Fauchoux; Carey J. Simonson (Energy and Buildings, 2024)

Hexavalent chromium still a concern in Sweden – Evidence from a cross-sectional study within the SafeChrom project - Zheshun Jiang; Linda Schenk; Eva Assarsson; Maria Albin; Helen Bertilsson; Eva Dock; Jessika Hagberg; Lovisa E. Karlsson; Pete Kines; Annette M. Krais; Stefan Ljunggren; Thomas Lundh; et al. (International Journal of Hygiene and Environmental Health, 2024)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Screening and characterization of antiviral compounds from Enteromorpha flexuosa against white spot syndrome virus (WSSV) and its in vivo influence on Indian white shrimp Fenneropenaeus indicus - S. Velmurugan; N. Jerin; M. Michael Babu; F. Bindhu; S. Albin Dhas; T. Citarasu (Aquaculture International, 2015)

Death by Caffeine: Presumptive Malicious Poisoning of a Dog by Incorporation in Ground Meat - S. N. Tawde; B. Puschner; T. Albin; S. Stump; R. H. Poppenga (Journal of Medical Toxicology, 2012)

A study on the influence of selected Indian herbal active principles on enhancing the immune system in Fenneropenaeus indicus against Vibrio harveyi infection - P. Raja Rajeswari; S. Velmurugan; M. Michael Babu; S. Albin Dhas; K. Kesavan; T. Citarasu (Aquaculture International, 2012)